Amputation free survival and overall survival after either endovascular or surgical infrapopliteal revascularization in diabetic and non-diabetic CLTI patients - Koivunen, Veerakaisa (My University, 2019)
Peripheral artery disease is a clinical endpoint of atherosclerotic disease. One of its major risk factors, diabetes mellitus, has a strong association to especially infrapopliteal disease. Revascularization in the infrapopliteal region is most commonly performed for patients with critical limb threatening ischemia, the most advanced form of the peripheral artery disease. A revascularization treatment can be performed either as a surgical or an endovascular intervention. Due to the innovation of technology of the past decades and improved skills of the operating surgeons, endovascular therapy has become the procedure-of-choice for patients with infrapopliteal disease. However, the present literature on superiority between the approaches remain scarce. The aim of the present study was to evaluate the possible differences after infrapopliteal endovascular or open surgery revascularization. Further emphasis was drawn to evaluate whether the outcome of either intervention was affected by diabetes mellitus. The present study was a retrospective analysis of 1024 consecutive peripheral artery disease patients from Department of Vascular Surgery of Turku University Hospital. All patients had infrapopliteal revascularizations, amputations or a combination of both between years 2007-2015. This study indicates that endovascular treatment was more likely to precede amputation compared to bypass surgery in both diabetics and non-diabetics. In overall survival, no difference was found. Additionally, the presence of diabetes mellitus did not worsen the outcome of revascularization. This study shows that a well-performed infrapopliteal surgical bypass with autologous vein offers better limb salvage in the long-term compared to endovascular approach.
Keywords: peripheral artery disease, critical limb threatening ischemia, diabetes mellitus, revascularization